Identification and quantification of stilbenes (piceatannol and resveratrol) in passiflora edulis by-products - Krambeck, Karolline (2020)
Recently, studies on the by-products from the food industry, such as passion fruit seeds, have significantly increased, as these can have an added value, due to their properties, such as potential antioxidant activity. This study was conducted to determine the presence of piceatannol and resveratrol in various extracts of passion fruit (Passiflora edulis) seeds from Madeira Island and a commercial passion fruit oil was used as reference. The commercial oil and the extracts that were obtained by traditional Soxhlet method with ethanol and acetone did not reveal the presence of the two stilbenes, piceatannol and resveratrol. However, the extracts that were obtained by the ultrasound method showed significant amounts of piceatannol and resveratrol when compared with the commercial oil. The presence of these compounds indicates that this oil could have potential application in cosmetic and pharmaceutical industries, due to their proven antioxidant and anti-aging properties.